Identification and optimization of process parameters for the production of bioethanol from the fermentation of oil palm trunks SAP - Norhazimah, Abdul Halim (2012)
Oil palm trunk(OPT)is generated from the replantation of oil palm trees at every 25-30 years interval,left as troublesome waste as it becomes the source of infection to young oil palm trees.This OPT contains a high amount of ready-to-use sugar in the form of sap which can be directly fermented to the most fermentation products.The fermentation process for ethanol production from OPT sap was evaluated in order to produce larger amount of bioethanol.The feasibility of yeast S.cerevisiae to produce bioethanol from OPT sap was investigated along with the effect of different strains of S.Cerevisiae and different pretreated mediums.It was proven that yeast S.cerevisiae was able to produce bioethanol even though the OPT sap undergoes less pretreatment compared to the previous works done by the other reseachers.The highest bioethanol yield and productivity had been obtained by using S.Cerevisiae Kyokai no.7 in heat sterilized sap.The effects of temperature,initial pH,agitation rate,percentage inoculum and time of incubation were explored using 2-level full factorial design in order to find out the main factor that affecting bioethanol fermentation from the OPT sap.The factors of temperature,initial pH and agitation rate were chosen for optimization study based on the higher percentage contribution(>5 %)and lower p-values(<0.05) The influential factor was then optimized using rotatable central composite design under response surface methodology (RSM).The validation experiment in shake flask were also carried out and compared with lab-scale bioreactor 2 L).The bioethanol concentration improves with the temperature around 30-32oC, agitation rate 60-90 rpm and initial pH of 5.00 to 5.50.The optimum condition for obtaining highest bioethanol production was after 36 h of fermentation at; temperature of 31 oC,initial pH 5.42 and agitation rate 80 rpm.The bioethanol production of 25.98 /L was obtained using this optimal condition, which is 97.93 % of the value predicted by the models.In 2 L of bioreactor,about 26.60 g/l of bioethanol concentration was obtained which is 2.39 % deviation from the result in shake flask experiment. Analysis on the production capacity of the bioethanol fermentation from OPT sap showed that this OPT sap was comparable with other biomass in term of bioethanol production per hectare (944 liter of bioethanol per hectare of oil palm replantation) and annual production capacity. This can be improved by further study on optimization of nutrient and follow the recommended improvements.In conclusion,the process parameter for the production of bioethanol from OPT sap was successfully identified and optimized in this study.